2020
DOI: 10.1002/fes3.232
|View full text |Cite
|
Sign up to set email alerts
|

Faster leaf senescence after flowering in wet direct‐seeded rice was mainly regulated by decrease in cytokinin content as compared with transplanted‐flooded rice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…A more significant accumulation of photosynthetic matter (dry matter mass) can be achieved using higher planting densities at different stages. Similar results were reported by Liu et al [25], who reported a more substantial photosynthetic capacity of rice individuals. In the present study, the dry matter at the MS stage of N2B3 treatment was higher.…”
Section: Discussionsupporting
confidence: 91%
“…A more significant accumulation of photosynthetic matter (dry matter mass) can be achieved using higher planting densities at different stages. Similar results were reported by Liu et al [25], who reported a more substantial photosynthetic capacity of rice individuals. In the present study, the dry matter at the MS stage of N2B3 treatment was higher.…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon is also reported to occur in tomato plants [28]. Furthermore, Liu et al [29] found that faster leaf aging after the plant began to bloom was mainly due to a decrease in the cytokinin content of the leaves. The last two findings justified that senescence of the older leaves in L. acutangula plants was associated with flowering and fruiting activities.…”
Section: Resultsmentioning
confidence: 58%
“…The relationship between leaf Chl concentrations and SPAD-502 values has been demonstrated (Minolta 1989, Süß et al 2015. This device has been used to measure the leaf Chl concentration in Prunus virginiana L., Viburnum lentago L., Oryza sativa L., and Arabidopsis thaliana (Ling et al 2011, Donnelly et al 2020, Liu et al 2020. For each species, it is necessary to derive a calibration curve with the SPAD value and its corresponding Chl content (Li et al 2017, Primka andSmith 2019).…”
Section: Introductionmentioning
confidence: 99%